Sphinganine/sphingosine (SA/SO) ratio and intake of fumonisin contamianted tortillas in a Mexican population - Landeros, Patricia (2005)
The fumonisins are mycotoxins relevant due to their toxicological effects on animals and humans. Based on the current knowledge of the mechanism of action of fumonisins, the sphinganine/sphingosine (Sa/So) ratio is a valid biomarker of exposure in animal studies and could also be useful in human studies if the ratio correlate with fumonisin intake. The Sa/So ratio was evaluated in a Mexican population at three stages of maize based food (tortillas) consumption. A Sa/So ratio higher than 1 was found at the A (regular consumption) and C (re-assumption of the regular consumption) stages, while during the B (stopping of the tortillas consumption for two weeks) stage the Sa/So ratio was lower than 1. This report showed that there is an association between the intake of fumonisin contaminated maize based foods and the elevation of the Sa/So ratio in human samples. Mexican population is exposed with a continuous high consumption of maize based foods commonly contaminated with fumonisins.